Empowering Language Learners: Strategies for Enhancing Learner Autonomy in Vietnamese Tertiary EFL Education - Le, Thanh Thao; Hua, Hong Hieu (Faculty of Education and Teacher Training of IAIN Palopo, 2024)
This qualitative study investigates the strategies employed by Vietnamese tertiary English as a Foreign Language (EFL) teachers to enhance learner autonomy in communication skills. Set against the backdrop of Vietnam’s evolving educational landscape, the study is informed by the theoretical frameworks of learner autonomy and sociocultural theory. The research utilizes semi-structured interviews with nine EFL teachers from two institutions, encompassing novice, mid-career, and near-end career stages. The thematic analysis of the interview data revealed four key strategies: collaborative learning, integration of technology, reflective practices, and personalized learning approaches. These strategies were found to be prevalent across different teaching experience levels, each contributing uniquely to fostering learner autonomy. Collaborative learning emerged as a tool for enhancing peer interaction and self-directed learning, while technology integration was highlighted for extending learning beyond the classroom. Reflective practices were shown to deepen students’ self-awareness and critical thinking, and personalized learning approaches were noted for catering to individual learner needs and preferences. The study highlights the importance of adaptable, context-sensitive teaching strategies in promoting learner autonomy in EFL contexts. It suggests the need for educational environments that support collaborative, technology-enhanced, reflective, and student-centered learning.